Physics Education Students’ Perceptions of Infused Water as a Healthy Beverage Companion to the MBG Program in Schools - Dimas Ridho; Ekin Dwi Arif Kurniawan; Artika Zahra; Baddariah Khopipa Pulungan; Reiphandy Ananda Purba; Riski Aulia (Hydrogen: Jurnal Kependidikan Kimia, 2026)
The Free Nutritious Food Program (MBG) in Indonesia has primarily focused on solid food provision, leaving the beverage component largely unaddressed. Meanwhile, sugar-sweetened beverage (SSB) consumption among school-age children remains a significant public health concern. Infused water has emerged as a low-cost, low-sugar alternative that may complement MBG implementation. This study investigates the perceptions of Physics Education students (n = 33) at Universitas Negeri Medan toward the potential of infused water as a healthy beverage companion to MBG, using a descriptive quantitative survey design. A 20-item Likert-scale instrument was developed based on Bloom’s Revised Taxonomy across cognitive, affective, and behavioral dimensions, and validated through Pearson correlation (all r > 0.339) and Cronbach’s Alpha (α = 0.966). Results indicate generally positive perceptions: cognitive (M = 4.06, High), affective (M = 4.28, Very High), and behavioral (M = 3.91, High). The affective dimension yielded the highest mean, while the behavioral dimension was comparatively lower, suggesting that students support the concept but may have limited practical experience. These findings suggest that infused water may have potential as a science-based educational tool to promote healthy hydration habits within MBG; however, further studies involving broader samples and field trials are needed before wider implementation.